The Impact of Socioeconomic and Cultural Factors on Family Caregiver Burden in Cancer Patients: A Study in Ogbomoso, Nigeria - Ofuoma, Amoo Patience; Ncama, Busisiwe (Asian Pacific Journal of Cancer Care, 2024)
Introduction: Cancer is increasingly becoming a chronic disease, presenting significant challenges for both patients and their caregivers. This study investigated the factors influencing caregiver burden in cancer patients within selected teaching hospitals in Ogbomoso, Oyo State, Nigeria. Materials and Methods: A cross-sectional study was conducted using a combination of questionnaires and interviews among 120 respondents selected through stratified sampling. Data analysis employed logit regression modeling alongside descriptive statistics. Results: The logit regression model identified five statistically significant variables influencing caregiver burden: education (positive coefficient, 2.15), social support (positive coefficient, 2.76), communication (positive coefficient, 2.67), financial support (positive coefficient, 4.92), and socio-cultural beliefs (negative coefficient,-2.64). These findings suggest that higher levels of education, social support, communication, and financial support increased the likelihood of caregiver burden, while strong socio-cultural beliefs were associated with reduced caregiver burden. Conclusion: This study highlights the multifaceted nature of caregiver burden in cancer patients, emphasizing the influence of socioeconomic and cultural factors. Recommendations include regular assessments of caregiver stress, promotion of shared care responsibilities within families, and culturally sensitive interventions to address the unique challenges faced by caregivers in this context.